Inhabiting the Body(ies) in Female Soccer Players: The Protective Role of Positive Body Image - Godoy-Izquierdo, Débora; Díaz, Isabel (Frontiers in Psychology, 2021)
In a social and sports world dominated by weight-centred beliefs and highly exigent and gendered athletic and beauty body standards, the vulnerability for eating pathology, i.e., disordered eating and eating disorders (EDs), is elevated among women athletes. The aim of this study was to explore body image facets and ED risk among female athletes in masculinised sports such as soccer. Forty-five federated amateur female soccer players from Spain participated in this study, voluntarily complying with an extensive evaluation protocol on attitudes towards body and appearance and eating practices. The participants overall reported self-representations of their bodies that corresponded to their reality as athletes, but their body ideals were also more demanding in terms of low fat and muscularity, in association with the functionality of their body and the physical demands of their athletic activity. Despite having a fairly high positive body image and body satisfaction, they also expressed negative attitudes towards their bodies. Around 2 out of 10 players were at risk of suffering from an ED. Players with negative attitudes towards their bodies had an odd 12 times likely to develop an ED compared to those with lower self-devaluation, after adjusting for BMI and body perceptions (OR=12.3, p<0.01). On the contrary, players who appreciate their bodies and hold a positive body image had an odd 83% lower to suffer from eating pathology, after adjusting for BMI and body satisfaction (OR=0.17, p<0.05). Our findings support the healthy and protective role of positive body image in sports contexts. Body attitudes should be addressed in preventive and therapeutic efforts for reducing the prevalence of EDs in women’s sports, within both a “negative” and a “positive” paradigm of body image.